2021
DOI: 10.3390/cells10030676
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Modifiers of TDP-43: Inflammatory Activation of Astrocytes for Neuroinflammation

Abstract: Transactive response DNA-binding protein 43 (TDP-43) is a ubiquitously expressed DNA/RNA-binding protein linked to amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). TDP-43 has been implicated in numerous aspects of the mRNA life cycle, as well as in cell toxicity and neuroinflammation. In this study, we used the toxicity of the TDP-43 expression in Saccharomyces cerevisiae as an assay to identify TDP-43 genetic interactions. Specifically, we transformed human TDP-43 cDNAs of wild-type or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Primary astrocytes with TDP-43 inclusions accumulated more lipid droplets, activated aerobic glycolysis, and downregulated lactate transporters, resulting in decreased metabolic support for MNs and neurotoxicity (Velebit et al, 2020). TDP-43 inclusion in the cytoplasm also induced astrocyte inflammation and activation, secreting pro-inflammatory factors (IL-1β, IL-6, and TNFα) and causing neurodegeneration and neuroinflammation (Lee et al, 2020;Kim et al, 2021).…”
Section: Tar Dna-binding Protein 43 and Astrocytesmentioning
confidence: 99%
“…Primary astrocytes with TDP-43 inclusions accumulated more lipid droplets, activated aerobic glycolysis, and downregulated lactate transporters, resulting in decreased metabolic support for MNs and neurotoxicity (Velebit et al, 2020). TDP-43 inclusion in the cytoplasm also induced astrocyte inflammation and activation, secreting pro-inflammatory factors (IL-1β, IL-6, and TNFα) and causing neurodegeneration and neuroinflammation (Lee et al, 2020;Kim et al, 2021).…”
Section: Tar Dna-binding Protein 43 and Astrocytesmentioning
confidence: 99%
“…Recent studies have found that TDP-43 is regulated by nuclear localisation signal (NLS) and nuclear export signal (NES) motifs; apart from its neuronal regulation activity, it also constantly shuttles between the cytoplasm and the nucleus [14,15]. Transcription and splicing are also involved in the courses of neurons' differentiation and apoptosis to maintain the stability of mRNA, which are the neuronal activity response to modulate neuronal plasticity [16][17][18].…”
Section: The Research Development Of Ftd Neuropathological Featurementioning
confidence: 99%
“…Genetic screens for modifiers of TDP-43 toxicity in the yeast system identified proteins involved in TDP-43 on toxicity [ 3 , 11 , 12 , 13 , 14 , 15 ]. Indeed, the finding that deletion or overexpression of PBP1, respectively reduces or enhances TDP-43 toxicity led to the discovery that PBP1′s human homolog, ATXN2 , is associated with ALS risk.…”
Section: Introductionmentioning
confidence: 99%